Ketimpangan Pemanfaatan Orbit Geostasioner (GSO) dalam Lingkungan Sistem Dunia - Deden Habibi Ali Alfathimy; Totok Sudjatmiko; Euis Susilawati (Departemen Hubungan Internasional, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Padjadjaran, 2019)
This article aims to analyze the inequality of geostationary orbits (GSO) utilization in world-system environment using World-systems Theory through qualitative-descriptive analysis. The high level of difficulty in mastering GSO technologies makes countries that do not have financial capacities and space capabilities inevitably use developed countries’ GSO satellite products. Based on historical and conceptual approach of the World-systems Theory, the results of the analysis show that inequality of the utilization of GSO is caused by and impacts on the persistence as well as revision of relations among countries in a world-system environment. Class struggle is an action taken naturally by semi-peripheral and periphery countries, including Indonesia, to revise the world-system environment through enhancing autonomy and promote more equitable regulations in GSO utilization.